Surgical Procedure in the Treatment of Organized Chronic Subdural Hematoma: A Single-Center Experience - Chen, Keng; Wang, Kun; Chen, Danzhi; Niu, Huanjiang; Yang, Shuxu; Wang, Yirong (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background Organized chronic subdural hematoma (CSDH) is a special type of CSDH. However, the optimal surgical procedure has not been established. We present our experience here to discuss the surgical procedure in treatment of organized CSDH.Methods Thirty-three patients with organized CSDH were admitted between January 1, 2008 and January 1, 2018. Age, gender, clinical symptoms, imaging data, type of surgical procedure, Barthel index (BI), and postoperative complications were collected and retrospectively analyzed. The BI was assessed both pre and postoperatively (1 week and 1 month after surgery).Results Overall, 14 patients underwent large craniotomy and 19 patients underwent small craniotomy. No significant differences in gender, age, initial clinical symptoms, and preoperative BI were found between the groups (p > 0.05). Among the 14 patients who underwent large craniotomy, 2 patients developed epilepsy after the operation, while 1 patient had postoperative aphasia. None of the patients had recurrence in 6 months postoperatively. Among the 19 patients who underwent small craniotomy, 1 patient developed an acute subdural hematoma and 1 patient developed aphasia. No obvious complications were found in the remaining 18 patients and none of the 19 patients had recurrence in 6 months postoperatively. BI scores of the small craniotomy group were significantly better than those of the large craniotomy group at 1 week postoperatively (p < 0.05). However, there was no significant difference in the 1-month results (p > 0.05).Conclusion According to our single-center experience, a small craniotomy for treating organized CSDH can be considered as an alternative to a larger craniotomy.
Keywords: organized chronic subdural hematoma; surgical procedure; Barthel index; postoperative complication